2016
DOI: 10.1002/cbdv.201500065
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Plants from the Genus Ixora

Abstract: Ixora is a genus of ca. 400 species in the family Rubiaceae. Since the 1940s, eighty-one compounds including phenolics, peptides, terpenoids, and sterols have been isolated from six species of the genus Ixora. Pharmacological studies have shown that these compounds and extracts from the Ixora genus have extensive activities, such as antitumor, chemoprotective, and antioxidant activities. In this review, we summarize the phytochemical progress and list the compounds isolated from the genus Ixora. The biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Three known compounds (scopoletin, isofraxidin, and geniposidic acid) were detected and isolated from the extracts of Ixora and Greenea species. Scopoletin ( 1 ) is a widely distributed coumarin found in a number of plant families such as Rutaceae and Apiaceae (Jain & Joshi, 2012), Clusiaceae (Marcondes et al, 2015), Convolvulaceae (Sood, Pradhan & Biswasroy, 2014; Khan & Hossain, 2015; Ojha, Mishra & Mishra, 2016), Solanaceae (Valizadeh et al, 2014), Asteraceae (Adams, Efferth & Bauer, 2006), Burseraceae (Mogana, Teng-Jin & Wiart, 2013), Asclepiadaceae (El-Demerdash et al, 2009), and Rubiaceae (Swe, 2008; Mohammed et al, 2013; Chen, Zhang & Chen, 2016). Isofraxidin ( 2 ) is found in species of Araliaceae (Maruyama et al, 2008; Yamazaki & Tokiwa, 2010; Bai et al, 2011; Lee et al, 2013), Asteraceae (Kwak, Lee & Schmitz, 2001; Gliszczyńska & Brodelius, 2012; Yim et al, 2017), Apiaceae (Yim et al, 2017), Simaroubaceae (Hwang et al, 2012), Rutaceae (Brown et al, 1988), Chloranthaceae (Niu et al, 2012; Li et al, 2016), and Rubiaceae (De Araújo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three known compounds (scopoletin, isofraxidin, and geniposidic acid) were detected and isolated from the extracts of Ixora and Greenea species. Scopoletin ( 1 ) is a widely distributed coumarin found in a number of plant families such as Rutaceae and Apiaceae (Jain & Joshi, 2012), Clusiaceae (Marcondes et al, 2015), Convolvulaceae (Sood, Pradhan & Biswasroy, 2014; Khan & Hossain, 2015; Ojha, Mishra & Mishra, 2016), Solanaceae (Valizadeh et al, 2014), Asteraceae (Adams, Efferth & Bauer, 2006), Burseraceae (Mogana, Teng-Jin & Wiart, 2013), Asclepiadaceae (El-Demerdash et al, 2009), and Rubiaceae (Swe, 2008; Mohammed et al, 2013; Chen, Zhang & Chen, 2016). Isofraxidin ( 2 ) is found in species of Araliaceae (Maruyama et al, 2008; Yamazaki & Tokiwa, 2010; Bai et al, 2011; Lee et al, 2013), Asteraceae (Kwak, Lee & Schmitz, 2001; Gliszczyńska & Brodelius, 2012; Yim et al, 2017), Apiaceae (Yim et al, 2017), Simaroubaceae (Hwang et al, 2012), Rutaceae (Brown et al, 1988), Chloranthaceae (Niu et al, 2012; Li et al, 2016), and Rubiaceae (De Araújo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, each plant part might possess different bioactive compounds that allow for different applications. To date, a few phytochemical studies of Ixora species have reported the presence of alkaloids, anthraquinones, phenolics, peptides, terpenoids, sterols, and iridoid glycosides (Chen, Zhang & Chen, 2016; Usha, Reginald & Immanuel, 2016). However, while there are several reports on the biological activities of extracts from Ixora species, only a handful of studies have identified their bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%